EFFECTIVE PRICING MANAGEMENT, A CATALYST FOR ENHANCING PROFITABILITY - Odunlami, Ibojo Bolanle (European Scientific Journal, ESJ, 2014)
The issue of pricing as a vital element of the marketing mix variables cannot be ignored when considering factors that boost organizational profitability. It interacts with other marketing mix variables in determining the collective efficacy of the marketing mix. Pricing is a vehicle for driving the effectiveness of other marketing mix variables. The objective of their paper is to determine if effective pricing management serves as catalyst for enhancing organizational profitability, using PZ Cussons Nigeria Plc. The method used is survey approach which gives room for primary data – questionnaire. Aside from the primary source of data, secondary source of data which includes the use of related literature materials, journals that are useful for the successful write up of this paper was adopted. In conclusion, it is an undisputable fact that pricing is a vital element of the marketing mix variables that determines the company’s sales volume and profitability. More so, it is a manipulative tool in the hand of organization’s influencing consumer decisions. In line with this research, it is hereby recommended that organizations should constantly pay attention to the pricing procedure as well as the reactions of potential buyers. More so, companies should be sensitive to competitors pricing strategies.